Impacto del estrés laboral en el desempeño de los servidores públicos del Instituto Ecuatoriano de Seguridad Social del Cantón Chone - Villacres Esmeralda, Carlos Julio (2020)
The purpose of this study was to determine the impact of work stress on the performance of public servants of the Ecuadorian Institute of Social Security of the Chone canton for the strengthening of the institution, whose methodology was inductive, deductive and analytical; that served as tools to obtain knowledge regarding the existing problem. For the collection of information, the interview technique was applied to the director of the IESS, an instrument that helped to know relevant issues of the institution that contributed to the investigation. In this study we worked with a population of 335 people who work in the different units of the establishment, to whom the “Medic-stress” survey was applied, which obtains scores in the study subjects of: mild, moderate, severe stress; obtaining as a result a severe level of work stress in the public servants of the IESS, where the organizational, individual, interpersonal, psychological factors among which are: the lack of personnel, the overload of work, the increase in responsibilities, the increase of absenteeism from work and being in constant contact with the anxieties and deaths of patients; they are exhibited as the main factors causing work stress, which is later reflected in a decrease in job performance, deterioration in health, loss of job satisfaction and the quality of service provided by the entity; therefore, the proposal of preventive techniques is proposed.